Role of Samagni and Kalbhojan in Deerghjeevanam- A Survey Study. - Kausar, Heena; Yadav, Nisha; Dixit, Mahesh; Khathuria, Diksha (International Research Journal of Ayurveda & Yoga, 2022)
Health is a state of complete physical, mental and social wellbeing and not merely an absence of disease or infirmity. Each and every person wants disease free life but unfortunately, we suffered from some sort of disease or discomfort amongst which lifestyle disorders are prominent one due to increasing sedentary life style and unhealthy eating habits. The qualities of healthy individual are narrated in Ayurveda as equilibrium of all three Doshas; Normal state of Jatharaagni, normal state and function of Dhathus (Tissues); Normal state and function of Malas; Pleasant soul, mind and sense objects. In present survey study 1500 people with age group 60 yrs or more were enrolled and association of longevity of life with healthy eating habits was assessed on questionaries’ basis which has reference in text for longevity. This survey study was conducted in Madan Mohan Malviya Govt. Ayurveda college Udaipur, Rajasthan. In the presence study different parameters were considered amongst which kaalbhuksevan and role of samagni in longevity of life is assessed here. Results found on statical basis that those people with state of samagni and habit of kalbhuk were found with age 60 or more without any associated complicating life style disorder. Which indicates positive results in association of samagni and kalbhuk with longevity of life as given in Ayurveda classics.